About the Routes of Teacher Training and Their Institutionalization - Poviliūnas, Arūnas (Acta Paedagogica Vilnensia, 2020)
The article compares a concurrent route and a consecutive route of teachers’ training and critically evaluates their institutionalization. The analysis of the practices of institutionalization (study processes, certification of the studies, higher education institutions, study grants, and the classification of the study programmes and sciences) reveals that the contemporary political power supports the concurrent route of teacher training.
Keywords: teacher training; concurrent and consecutive routes; institutionalization